Novel insights into actions of bisphosphonates on bone: differences in interactions with hydroxyapatite. - Nancollas, G; Tang, R; Phipps, R; Henneman, Z; Gulde, S; Wu, W; Mangood, A; Russell, R; Ebetino, F (2006)
Bisphosphonates are now the most widely used drugs for diseases associated with increased bone resorption, such as osteoporosis. Although bisphosphonates act directly on osteoclasts, and interfere with specific biochemical processes such as protein prenylation, their ability to adsorb to bone mineral also contributes to their potency and duration of action. The aim of the present study was to compare the binding affinities for hydroxyapatite (HAP) of 6 bisphosphonates currently used clinically and to determine the effects of these bisphosphonates on other mineral surface properties including zeta potential and interfacial tension. Affinity constants (K(L)) for the adsorption of bisphosphonates were calculated from kinetic studies on HAP crystal growth using a constant composition method at 37 degrees C and at physiological ionic strength (0.15 M). Under conditions likely to simulate bisphosphonate binding onto bone, there were significant differences in K(L) among the bisphosphonates for HAP growth (pH 7.4) with a rank order of zoledronate > alendronate > ibandronate > risedronate > etidronate > clodronate. The measurements of zeta potential show that the crystal surface is modified by the adsorption of bisphosphonates in a manner best explained by molecular charges related to the protonation of their side-chain moieties, with risedronate showing substantial differences from alendronate, ibandronate, and zoledronate. The studies of the solid/liquid interfacial properties show additional differences among the bisphosphonates that may influence their mechanisms for binding and inhibiting crystal growth and dissolution. The observed differences in kinetic binding affinities, HAP zeta potentials, and interfacial tension are likely to contribute to the biological properties of the various bisphosphonates. In particular, these binding properties may contribute to differences in uptake and persistence in bone and the reversibility of effects. These properties, therefore, have potential clinical implications that may be important in understanding differences among potent bisphosphonates, such as the apparently more prolonged duration of action of alendronate and zoledronate compared with the more readily reversible effects of etidronate and risedronate.